Genetic variability for Alternaria leaf blight resistance in groundnut genotypes: Genetic variability for Alternaria leaf blight resistance in groundnut genotypes - NARENDRA KUMAR; B C AJAY; K S JADON; K GANGADHARA; PRAVEEN KONA; A L RATHANAKUMAR; T RADHAKRISHNAN; B M CHIKANI (Journal of Oilseeds Research, 2020)
Fifty genotypes were screened for resistance to Alternaria leaf blight during three successive summer seasons during 2013 to 2015. Pooled analysis of variance indicated significant genotypic differences observed for resistance of Alternaria leaf blight indicating the existence of genetic variability among the 50 genotypes. Alternaria leaf blight had high heritability coupled with high genetic advance as per cent of mean revealed selection would be effective for improving this trait in studied genotypes. Based on three year data two advanced breeding lines viz., PBS-12169, PBS-12190 found resistance to Alternaria leaf blight. These genotypes can be used in breeding programme for developing high yielding groundnut cultivars resistance to Alternaria leaf blight.